Inhibition of Tryptophan Hydroxylases and Monoamine Oxidase-A by the Proton Pump Inhibitor, Omeprazole—In Vitro and In Vivo Investigations - Betari, Nibal; Sahlholm, Kristoffer; Morató, Xavier; Godoy-Marín, Héctor; Jáuregui, Olga; Teigen, Knut; Ciruela, Francisco; Haavik, Jan (Frontiers in Pharmacology, 2020)
Serotonin (5-HT) is a hormone and neurotransmitter that modulates neural activity as well as a wide range of other physiological processes including cardiovascular function, bowel motility, and platelet aggregation. 5-HT synthesis is catalyzed by tryptophan hydroxylase (TPH) which exists as two distinct isoforms; TPH1 and TPH2, which are responsible for peripheral and central 5-HT, respectively. Due to the implication of 5-HT in a number of pathologies, including depression, anxiety, autism, sexual dysfunction, irritable bowel syndrome, inflammatory bowel disease, and carcinoid syndrome, there has been a growing interest in finding modulators of these enzymes in recent years. We thus performed high-throughput screening (HTS) using a fluorescence-based thermal shift assay (DSF) to search the Prestwick Chemical Library containing 1280 compounds, mostly FDA-approved drugs, for TPH1 binders. We here report the identification of omeprazole, a proton pump inhibitor, as an inhibitor of TPH1 and TPH2 with low micromolar potency and high selectivity over the other aromatic amino acid hydroxylases. The S-enantiomer of omeprazole, esomeprazole, has recently also been described as an inhibitor of monoamine oxidase-A (MAO-A), the main enzyme responsible for 5-HT degradation, albeit with lower potency compared to the effect on TPH1 and TPH2. In order to investigate the net effect of simultaneous inhibition of TPH and MAO-A in vivo, we administered high-dose (100 mg/kg) omeprazole to CD-1 mice for 4 days, after which the animals were subjected to the tail suspension test. Finally, central (whole brain) and peripheral (serum) 5-HT content was measured using liquid chromatography-mass spectrometry (LC-MS). Omeprazole treatment significantly increased 5-HT concentrations, both in brain and in serum, and reduced the time spent immobile in the tail suspension test relative to vehicle control. Thus, the MAO-A inhibition afforded by high-dose omeprazole appears to overcome the opposing effect on 5-HT produced by inhibition of TPH1 and TPH2. Further modification of proton pump inhibitor scaffolds may yield more selective modulators of 5-HT metabolism.